2004
DOI: 10.1111/j.1048-891x.2004.14545.x
|View full text |Cite
|
Sign up to set email alerts
|

Small cell carcinoma of the endometrium: report of three cases and literature review

Abstract: Although the prognosis of small cell carcinoma of endometrium is poor, early detection of this disease may contribute to an improved prognosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
1

Year Published

2009
2009
2017
2017

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(23 citation statements)
references
References 17 publications
2
20
1
Order By: Relevance
“…The average patient age at the time of diagnosis has been reported to be 60 years old, which is 10 years older than the age for endometrial adenocarcinoma [9]. Endometrial small cell carcinoma, a rare neuroendocrine tumor, tends to develop in women with parity greater than two and presents with vaginal bleeding as the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average patient age at the time of diagnosis has been reported to be 60 years old, which is 10 years older than the age for endometrial adenocarcinoma [9]. Endometrial small cell carcinoma, a rare neuroendocrine tumor, tends to develop in women with parity greater than two and presents with vaginal bleeding as the most common symptom.…”
Section: Discussionmentioning
confidence: 99%
“…The FIGO stage of the disease is the most important prognostic factor [3]. In a literature review, Katahira et al [9] found that only 23% (3/13) of the patients with stage I disease died of the disease within 5 years. By contrast, 73% (17/22) of patients with stages IIeIV disease died within 2 years of diagnosis.…”
Section: Discussionmentioning
confidence: 99%
“…Histopathologic diagnosis was based on morphologic criteria following hematoxylin-eosin (H-E) staining (Albores-Saavedra et al 1997;Ishida et al 2004;Katahira et al 2004 (Chang et al 1999). This study to analyze the case series was approved as a retrospective study by our institutional review board.…”
Section: Patientsmentioning
confidence: 99%
“…it has been reported that both SCC and endometrioid adenocarcinoma of the endometrium express vimentin [1,8,9]. in contrast, vimentin is expressed in adenocarcinoma of the lung, but not in SCC of the lung [10].…”
Section: Immunohistochemistrymentioning
confidence: 99%